Powoływanie Administratora Bezpieczeństwa Informacji jako zasada bezpiecznego przetwarzania danych na gruncie ustawy o ochronie danych osobowych - Wygoda, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
On January 1, 2015 amendments changing the legal status of the Administrator of Personal Data Security Pol. Administrator Bezpieczeństwa Informacji, hereinafter “ABI” were introduced into the Polish Law on Personal Data Protection. Description of the legal consequences of one of the amendments is the subject of the analysis included in this text.The main theme of the analysis is an attempt to answer the question whether appointing of this person is up to the free decision of a personal data protection administrator or if the decision is subject to certain conditions. Addressing the issue begins with a concise description of a position and role dedicated to ABI in the processing of personal data. Next, there is an indication of the scope of responsibilities entrusted to him. On this background are projected, from the historic perspective, the views of the legal doctrine and judicature on appointing ABI. The consequent linguistic and functional analysis of normative grounds for ABI appointment after the amendment allowed to indicate the scope of discretion in his appointment.
Keywords: Administrator Bezpieczeństwa Informacji; przetwarzanie danych; ustawa o ochronie danych osobowych